Cluster formation at the Si/liquid interface in Sr and Na modified Al–Si alloys. (May 2016) - Barrirero, Jenifer; Li, Jiehua; Engstler, Michael; Ghafoor, Naureen; Schumacher, Peter; Odén, Magnus; Mücklich, Frank
Abstract: Atom probe tomography was used to compare Na and Sr modified Al–Si hypoeutectic alloys. Both Na and Sr promote the formation of nanometre-sized clusters in the Si eutectic phase. Compositional analyses of the clusters show an Al:Sr ratio of 2.92 ± 0.46 and an Al:Na ratio of 1.07 ± 0.23. It is proposed that SrAl2 Si2 and NaAlSi clusters are formed at the Si/liquid interface and take part in the modification process by altering the eutectic Si growth. Graphical abstract: